Can Lucifer Yellow Indicate Correct Permeability of Biological Cell Membrane under An Electric and Magnetic Field? - Tahereh Pourmirjafari Firoozabadi (Cell Journal, 2015)
The effect of external magnetic and electric fields, in the range of electroporation and magnetoporation, on Lucifer Yellow (LY) fluorescence in the absence of cells is studied. Electric-field-induced quenching and magnetic field-induced increase are observed for fluorescence intensity of LY. Regard to the fact that the variation of field-induced fluorescence, even in the absence of cells, can be observed, the application of LY, as a marker, is debatable in electroporation and magnetoporation techniques.